(3LRA ef GdbQBf GdcQjes - (3cdGe Gddg YR hLds
(3ChdgG (B:s
(3bGd JYGdi (B: ( (3cd GdWYGe cGf MdkG dHfi ESQGFjd EdG eG MQe ESQGFjd Ydi faSg (B) s
(3BNQgG (B:s
(3bGd JYGdi (B( (3hEf JLeYhG Hjf GdCNJjf EdG eG bO Sda Ef Gddg cGf ZahQkG QMjekG (B) (3UOb Gddg GdYXje s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdcJH GdSeGhjIs